Fresh volcanic aerosols injected in the atmosphere during the volcano eruptive activity at the Cumbre Vieja area (La Palma, Canary Islands): Temporal evolution and vertical impact. (1st May 2023) - Córdoba-Jabonero, Carmen; Sicard, Michaël; Barreto, África; Toledano, Carlos; López-Cayuela, María Ángeles; Gil-Díaz, Cristina; García, Omaira; Carvajal-Pérez, Clara Violeta; Comerón, Adolfo; Ramos, Ramón; Muñoz-Porcar, Constantino; Rodríguez-Gómez, Alejandro
Abstract: For the first time in fifty years, the Cumbre Vieja volcanic area (La Palma, Canary Islands, Spain) erupted on September 19, 2021, giving birth to a new volcano. Fresh volcanic aerosols were continuously injected into the troposphere at different height levels, decreasing with time until the end of December 2021 (15 weeks duration). A wide set of different instrumentation was deployed all over the Island in order to evaluate the effects of the volcanic plumes on the atmosphere and the air quality. For the first time, a long-term study of the relative mass contribution and vertical impact of the volcanic components, ash and non-ash particles separately, during the eruptive activity was carried out in this work. In particular, a polarized Micro-Pulse Lidar (P-MPL) was deployed at Tazacorte (at around 8 km west from the volcano) in 24/7 operation from October 17, 2021 until the end of the volcano activity (11 weeks) for vertical monitoring of the volcanic particles. First, a statistical study of the mass conversion factors for mass concentration estimation of the volcanic (ash and non-ash) particles was performed by using the AERONET sun/sky-photometer dataset at Fuencaliente (at around 18 km south from the volcano). A representative mass conversion factor was obtained for ash and non-ash particles: 1.89 ± 0.53 and 0.31 ± 0.06 g m −2, respectively, with no dependence on time and optical depth. Second, these factors were used to calculate the ash and non-ash mass concentrations from P-MPL observations. Ash particles dominated 11% of the time and mostly until week 3 (i.e. week 7 from the volcanic eruption). Their mass concentration decreased by one order of magnitude: the relative ash mass contribution was 73 ± 18% with a total mass loading of 566 ± 281 mg m −2 at week 1, reducing gradually down to 38 ± 32% and 120 ± 49 mg m −2, respectively, at week 11. Layer-to-layer, it decreased with increasing layer-height; no ash was detected above 4 km at the end of the volcanic period. Third, in order to analyse the potential AERONET underestimation of the coarse mass conversion factor due to the 15 μm cutoff effect in the AERONET retrieval, two worst-case-scenarios (WCS) were examined, representing aged-like ash particles (WCS1, 4-μm radius) and fresh-like (WCS2, 10-μm radius). For both scenarios, the mass concentration of the volcanic plumes exceeded the first contamination level (>200 μg m −3, as defined by the UK Meteorological Office) up to 5–6 km height mostly during week 1 and up to 1–2 km until week 9. The extreme contamination level (>2000 μg m −3, aircraft flight limitations) was only exceeded from week 1 to week 6 under WCS2 conditions. This work infers a new long-term insight on the volcanic matter injected in the atmosphere with relevance for Air Quality issues and air traffic safety policies. Graphical abstract: Image 1 Highlights: A long-term on-site study during Cumbre Vieja volcano activity in 2021 is performed. Fresh ash and non-ash particles examined separately using remote sensing observations. Representative mass conversion factors estimated for both fresh volcanic components. Evolution and final decay of ash particles regarding their vertical mass contribution. Vertical ash impact related to contamination levels for AQ and aircraft operations.